Dampak Environmental Performance dan Environmental Disclosure terhadap Profitabilitas Perusahan - Sparta Sparta; Dita Ayu (STIE Indonesia Banking School, 2016)
This study aimed to examine the impact of environmental performance and environmental disclosure to profitability. Profitability is measured by Return on Asset, environmental performance by PROPER Rating, while environmental disclosure by Corporate Disclosure Indeks. This research also used size and leverage as control variables. Samples generated from The SRI-HATI index from 2010 to 2014, which in total 50 observations. The research proves that the environmental performance, company size and leverage have a significant negative impact on profitability, while environmental disclosure does not impact on the profitability of the company. These results have implications especially to companies and investors related to the costs incurred by the company for improvement of environmental performance and disclosure.